Measurement of small misorientations using electron back scatter diffraction - Wilkinson, A (1999)
This paper concerns the determination of small misorientations using electron back scatter diffraction (EBSD). Generally EBSD is used to measure crystal orientations from which misorientations can be calculated. Repeated measurements on undeformed Si showed that the calculated misorientations have an error of +/- 0.25 degrees associated with the misorientation angle, while the misorientation axis generally has a larger error. The uncertainty in the calculated misorientation axis increases significantly as the misorientation angle decreases, so that for misorientation angles below similar to 5 degrees the misorientation axis is essentially undetermined. A new method in which the misorientation is measured directly from a pair of EBSD patterns is presented. The analysis uses a cross-correlation procedure to determine the relative positions of two or more similar features in the pair of EBSD patterns. Measurements from a Si specimen deformed in single slip indicate that the new method gives reliable misorientations (axis and angle) for misorientations of similar to 0.25 degrees or greater.